2017
DOI: 10.19071/cb.2017.v8.3265
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Some Important Fodder Plants of Joshimath area of Chamoli District of Garhwal, Uttarakhand

Abstract: India has more than 13% of the total livestock population of the world, but it does not have specially identified and regularly managed pastures. Although about 12 million ha of the land in the country is officially recorded as the grazing land, a vast majority of the population depends on the forest for fodder. Livestock is considered as one of the main sources of livelihood, which depends mostly on fodder. Fodder is extracted from forests, grasslands, agricultural land, and agroforestry practices. Agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Protein, phosphorus, and calcium are very important for milk producing animals [38]. Ficus species are the main fodder tree species that are lopped during summer season to feed the animals [39]. In the present study, it was observed that value of ash content, protein, and calcium except phosphorous of leaf of F. palmata was relatively high compared to other species [40].…”
Section: Nutritive Valuementioning
confidence: 48%
“…Protein, phosphorus, and calcium are very important for milk producing animals [38]. Ficus species are the main fodder tree species that are lopped during summer season to feed the animals [39]. In the present study, it was observed that value of ash content, protein, and calcium except phosphorous of leaf of F. palmata was relatively high compared to other species [40].…”
Section: Nutritive Valuementioning
confidence: 48%
“…On the potential of trees for green fodder some notable contributions have been made including Nautiyal et al, (2017), Nunes et al, (2015) V. Singh et al, (2008). During present study, attempts have been made to enlist the noncultivated fodder plant species which are commonly used for cattle, with the concept of better utilization of forage in livestock feeding growing in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier studies revels that browses have multiple roles in farming systems such as fodder and veterinary medicines (Luseba & Van Der Merwe, 2006). In Uttarakhand, forests and other uncultivated lands play a key role in the livelihood system of hills, as they provide firewood, fodder (in form of grazing fields and forage) for livestock and agricultural implements and a variety of medicinal plants and other non-timber forest produce for local consumption (Nautiyal et al, 2017). As a major source of animal feeds, fodder trees and shrubs are highly valued by farmers, in order to provide the nutritional needs.…”
Section: Introductionmentioning
confidence: 99%
“…Tree and shrub leaves are significant component of small ruminant diets in several portions of the world and play a vital role in nutrition of browsing animals in areas where insufficient or no replacements are available (Gxasheka et al, 2015). Nutrient contents are impartially high in all fodder tree species though, their quantity varies markedly from one species to alternative (Nautiyal et al, 2017). Dissimilarities in nutrient contents in an individual species also occur with the alteration in season.…”
Section: Introductionmentioning
confidence: 99%